Stress information - do we perceive health risks? - Wioletta Jachym (University of Applied Sciences in Tarnow, Poland, 2017)
The main aim of this article is to characterise information stress as a form of stress connected with the development of the information society. An intermediate goal is to point to the mechanism of its formation and possible health consequences. The article was prepared with the use of critical analysis of literature, whereby the definitions of biological, psychological and information stress were demonstrated. Stressors associated with the incidence of information stress were shown. The review of publications indicates interest in the phenomenon of information stress from the fields of psychology and information science.The theoretical reflections on information stress are the basis for empirical research in this field.